(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article presents a lecture material on the study of the morphofunctional characteristics of the skin and its derivatives, which are included in the modern spectrum of active and interactive forms of histology education in order to effectively form the professional competence of future doctors of the specialties "Medicine", "Pediatrics" and "Dentistry", as well as students of biological faculties.